Handbook of interview research - Gubrium, Jaber F.; Holstein, James A.; Sage eBooks (Thousand Oaks, [Calif.] ; London : SAGE, 2002)
Aimed at professionals in market research and journalism as well as researchers, academics and students, this handbook is both an encyclopedia providing discussions of methodological issues and a story of a particular tale of interviewing.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Interviewing -- Handbooks, manuals, etc; Electronic books